Galaxy and mass assembly: the 1.4 GHz SFR indicator, SFR–M* relation and predictions for ASKAP–GAMA - Davies, L; Huynh, M; Hopkins, A; Seymour, N; Driver, S; Robotham, A; Baldry, I; Bland-Hawthorn, J; Bourne, N; Bremer, M; Brown, M; Brough, S; et al. (Oxford University Press, 2016)
We present a robust calibration of the 1.4 GHz radio continuum star formation rate (SFR) using a combination of the Galaxy And Mass Assembly (GAMA) survey and the Faint Images of the Radio Sky at Twenty-cm (FIRST) survey. We identify individually detected 1.4 GHz GAMA-FIRST sources and use a late-type, non-AGN, volume-limited sample from GAMA to produce stellar mass-selected samples. The latter are then combined to produce FIRST-stacked images. This extends the robust parametrisation of the 1.4 GHz-SFR relation to faint luminosities. For both the individually detected galaxies and our stacked samples, we compare 1.4 GHz luminosity to SFRs derived from GAMA to determine a new 1.4 GHz luminosity-to-SFR relation with well constrained slope and normalisation. For the first time, we produce the radio SFR-M⇤ relation over 2 decades in stellar mass, and find that our new calibration is robust, and produces a SFR-M⇤relation which is consistent with all other GAMA SFR methods. Finally, using our new 1.4 GHz luminosity-to-SFR calibration we make predictions for the number of star-forming GAMA sources which are likely to be detected in the upcoming ASKAP surveys, EMU and DINGO.